PENGARUH BURNOUT DAN SELF EFFICACY TERHADAP KINERJA DOSEN PASCASARJANA UIN ALAUDDIN MAKASSAR - Gemely, Delfina (Inspiratif Pendidikan, 2020)
The objectives of the study were to determine: 1. The influence of burnout on the Postgraduate lecturers’ performance of UIN Alauddin Makassar, 2. The influence of self-efficacy on the Postgraduate lecturers’ performance of UIN Alauddin Makassar, 3. The influence of burnout and self-efficacy on the Postgraduate lecturers’ performance of UIN Alauddin Makassar. The study was the quantitative research with ex-post facto method, conducted at the Postgraduate of UIN Alauddin Makassar. The total number of population of lecturers at the Postgraduate of UIN Alauddin Makassar was 72 lecturers. Accidental sampling technique was employed in taking the samples of 30 lecturers. The instrument used to collect the data was a questionnaire, which then analyzed using descriptive and inferential statistical techniques (simple and multiple linear regressions). The results of the study through simple and multiple regression analysis revealed that there was a positive and significant influence of burnout on the lecturers’ performance with the t count> t table (2.315> 2.056) and a significance of 0.028 <0.05, so H1 was accepted. The coefficient of determination was observed at the value of R Square = 0.161 meaning that 16% of performance was explained by burnout and 84% of performance was influenced by other factors. There was no positive and significant influence of self-efficacy on performance with the value of t count <t table (1.574 <2.056) and the significance of 0.127> 0.05, so H1was rejected. The coefficient of determination was identified at the value of R Square = 0.081 meaning that 8% of the variability of the performance variable was explained by self-efficacy and 92% of the performance was influenced by other factors. For the third variable, there was a positive and significant influence of burnout and self- efficacy collaboratively on the lecturers’ performance with the value of F count > F table (3.758> 3.35) and a significance of 0.036 <0.05, so H1was accepted. The coefficient of determination was seen at the value of R Square = 0.218 meaning that 21.8% of the variability of the performance variable was explained by burnout and self-efficacy while 78.2% of the performance was influenced by other variables not included in this study. The implications of the study indicated that the existence of successful adaptation to stressful demands will prevent the appearance of burnout in working. The success of this adaptation exemplified the existence of self-efficacy that was the belief possessed to be able to achieve the objectives as expected.